ANALISIS BANJIR DAN TANAH LONGSOR TERKAIT PERUBAHAN TUTUPAN LAHAN DAN INDEKS VEGETASI DI KOTA BATU MENGGUNAKAN CITRA SATELIT MULTI-TEMPORAL - Fahrin Ajie Mahmud; Akbar Kurniawan (Jurnal Penginderaan Jauh Indonesia, 2025)
Natural disasters pose significant threats to communities, often resulting from natural factors and human activities, such as landslides and floods. In 2023, Indonesia experienced 5,400 disasters, with 99.35% being hydrometeorological events. Batu City, East Java, has seen an increase in disasters, particularly landslides and floods, indicating ecosystem disturbances due to land-use changes. This study employs multi-temporal satellite imagery data (Landsat-8 and Sentinel-2) from 2013 to 2023 to analyze land cover changes and vegetation indices. The maximum likelihood supervised classification method and the Normalized Difference Vegetation Index (NDVI) were utilized to map land cover and vegetation distribution. Results reveal significant land cover changes, with non-vegetated areas increasing by 189.291 hectares and vegetated areas decreasing by 177.477 hectares. These changes contribute to the rising incidence of landslides and floods, particularly in residential and agricultural areas. Spatio-temporal analysis demonstrates a correlation between land cover changes, vegetation indices, and disaster frequency, underscoring the importance of sustainable land management in mitigating disaster risks.